2022
DOI: 10.1021/acs.jpclett.2c01519
|View full text |Cite
|
Sign up to set email alerts
|

Stick or Spill? Scaling Relationships for the Binding Energies of Adsorbates on Single-Atom Alloy Catalysts

Abstract: Single-atom alloy catalysts combine catalytically active metal atoms, present as dopants, with the selectivity of coinage metal hosts. Determining whether adsorbates stick at the dopant or spill over onto the host is key to understanding catalytic mechanisms on these materials. Despite a growing body of work, simple descriptors for the prediction of spillover energies (SOEs), i.e., the relative stability of an adsorbate on the dopant versus the host site, are not yet available. Using Density Functional Theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…It is important to note however that this rule only holds when the binding trends between the adsorbate and the dopant are dominated by the sharing of electrons, i.e., covalent contributions. H2O and NH3 are known examples of adsorbates for which the binding trends are dominated by electrostatic interactions (20). At the electronic level, this translates to a limited reshuffling of the electronic density of H2O upon adsorption compared with NO (Fig.…”
Section: Extension To Molecular Fragments Their Geometry and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note however that this rule only holds when the binding trends between the adsorbate and the dopant are dominated by the sharing of electrons, i.e., covalent contributions. H2O and NH3 are known examples of adsorbates for which the binding trends are dominated by electrostatic interactions (20). At the electronic level, this translates to a limited reshuffling of the electronic density of H2O upon adsorption compared with NO (Fig.…”
Section: Extension To Molecular Fragments Their Geometry and Reactivitymentioning
confidence: 99%
“…Albeit faster than and as accurate as DFT calculations, these models do not provide the fundamental physical principles that govern the stability of adsorbates on SAA surfaces. In a change of perspective, a few studies have suggested to consider SAAs as analogues of molecular systems (17)(18)(19)(20). The stability of such systems is related to the filling of discrete states (atomic or molecular orbital) resulting in various electron-counting rules (octet, 4n+2 aromaticity rule, etc) (21)(22)(23).…”
mentioning
confidence: 99%
“… 19 While not necessarily associated with localized d states, charge transfer has recently been reported for several other SAAs in the literature as well. 37 With this in mind, intermetallics and alloys with localized d states may be worthwhile materials to consider if catalysts with anionic metals are desired. For instance, prior work has shown that single-atom catalysts with anionic metal centers are promising for several electrocatalytic reduction reactions.…”
mentioning
confidence: 99%
“…19 While not necessarily associated with localized d-states, charge transfer has recently been reported for several other SAAs in the literature as well. 35 With this in mind, intermetallics and alloys with localized d states may be worthwhile materials to consider if catalysts with anionic metals are desired. For instance, prior work has shown that single-atom catalysts with anionic metal centers are promising for several electrocatalytic reduction reactions.…”
mentioning
confidence: 99%